Biotransformation of Succinodinitrile into Corresponding High Value Compounds using Nitrile Hydrolysing Enzyme from Microbacterium paraoxydans RS15 - Sharma, Rohit; Smita, Madhu; Singh, Aakash Kumar (Asian Journal of Biological and Life Sciences, 2016)
A Gram-negative bacterial strain, identified as Microbacterium paraoxydans RS15 using 16S rRNA technique, has been used in the present study. Total 40 cultures screened through primary screening were further selected for secondary screening in shake flask containing MSM media and nitrile substrate. This strain was grown on a variety of aliphatic and aromatic nitriles (benzonitrile, Mandelonitrile, Propionitrile). This strain was grown well successfully on Succinodinitrile containing plates from 10mM to 200mM concentration. This isolate showed growth associated nitrile hydrolysing enzyme production after 11 h in bioreactor and 24 h of incubation in shake flask at optimal conditions. Enzyme activity increased to 1109 and 687 U/ml/mg when the media was supplemented with Glucose and Sodium Citrate respectively. Scale up of enzyme production was studied in 5L in-situ bioreactor. Bacterial cells when exposed to different solvents like Toluene, Hexane and Ethyl acetate showed a significant retention in nitrile hydrolysing enzyme activity and the maximum was in hexane. The kinetic characterization of the nitrile hydrolysing enzyme exhibited temperature optima at 30oC and pH 7. Biotransformation of succinodinitrile into corresponding high value compounds like Succinic acid and amide using nitrile hydrolysing enzyme from Microbacterium paraoxydans was carried out and the same was authenticated using analytical technique GC-MS.
Keywords: Biotransformation; In-situ bioreactor; Microbacterium paraoxydans; Nitrile hydrolysing enzyme